Popis kosca Crex crex v Sloveniji leta 1999 kaže na kratkoročno stabilno populacijo - Trontelj, Peter (Acrocephalus, 2001)
In the 1999 census of night-time singing Corncrakes in a priori identified areas, 563 singing males were counted. Taking into consideration yet unvisitedpotential singing sites, the total Slovenian population in 1999 was estimated at 590 singing male Corncrakes. The most important breeding areas were situated in south-central Slovenia (Ljubljansko barje, Lake Cerknica, Planina Polje, the Reka river valley, along the Nanoščica and Pivka rivers), where 79% of the bird's population was found. These areas are extensive karst poljes or geomorphologically related flat depressions between Dinaric mountainmassifs. Two other sites holding significant numbers of Corncrakes were Kobariški Stol (mountain in Western Julian Alps) with 41 and Jovsi (SE Slovenia, Pannonian plain) with 17 singing males. The total count increased by21% compared to the first national census in 1992/93. In part, the increase can be explained by more elaborate field work and better timing (exclusively by night, before first mowing in June). Since the error of the first census isnot known, the higher count cannot be unequivocally ascribed to a general population increase. During both censuses, the majority of sites held one or two Corncrakes only. Nevertheless, there were significant differences in change rates between the seven most important sites. Numbers increased on foursites (Kobariški Stol, Jovsi, Nanoščica basin, Reka valley), remained constant on two (Ljubljansko barje, Planina Polje), and decreased on one site (Lake Cerknica). There is no evidence that the decrease at Lake Cerknica was aconsequence of human impact.
Keywords: Birds; Populacijska gostota; Population density; Ptice; bird; Slovenia; Slovenija; ornitologija; kosec